Regional Conditions and Land-Use Alter the Potential Contribution of Soil Arthropods to Ecosystem Services in Grasslands - Birkhofer, Klaus; Dietrich, Christoph; John, Katharina; Schorpp, Quentin; Zaitsev, Andrey S.; Wolters, Volkmar (Frontiers in Ecology and Evolution, 2016)
We investigated the impact of regional conditions and land-use intensity on eight selected arthropod taxa of Mesostigmata (Parasitidae), Oribatida (3 species), Collembola (1 species), Chilopoda (2 species) and Diplopoda (1 species) sampled in differently managed permanent grasslands of three German study regions. By jointly analyzing changes in abundance and trophic behavior (measured as natural variation in 15N/14N and 13C/12C ratios) we intended to develop a framework for evaluating the impact of local and regional conditions on the ecosystem services delivered by soil animals (mainly decomposition- and predation-related services). The investigated taxa could be assorted to three major groups: (1) numerical response only, (2) numerical and trophic response and (3) trophic response only. Since the combination of taxa assembled in the individual groups does not correspond to any of the conventional soil ecological classification systems, this grouping offers a new approach for analyzing soil communities. The complementing consideration of both the direction of the numerical response and the type of the trophic response (change of the basal food source vs. trophic level shift vs. variations in isotopic niches) provided a differential insight into the effect of management and geographic differences on soil arthropods. It could be shown that the effect of land-use on the abundance of detritivorous microarthropods varies among regions, but does not induce any changes in feeding behavior. Our findings on Parasitidae indicate that carnivorous microarthropods exert substantial predation pressure on soil mesofauna and may be quite resistant to environmental changes due to high trophic flexibility. If conditions are favorable, centipedes may reach comparatively high densities in permanent grasslands and could be very important for controlling belowground pests. Concerning millipedes, isotopic signatures suggest that some species could exert a substantial disservice by feeding on roots over a wide range of land-use intensities and regional conditions. We conclude that the many consistent and significant effects found in our study support our contention that the combined analysis of numerical and trophic responses provides a promising framework for designing spatially explicit models that quantify the impact of human interventions on the delivery of ecosystem services by the soil fauna.